2014
DOI: 10.1007/s10571-014-0043-z
|View full text |Cite
|
Sign up to set email alerts
|

Gastrodin Inhibits Glutamate-Induced Apoptosis of PC12 Cells via Inhibition of CaMKII/ASK-1/p38 MAPK/p53 Signaling Cascade

Abstract: Previous research demonstrated that glutamate induces neuronal injury partially by increasing intracellular Ca(2+) concentrations ([Ca(2+)]i), and inducing oxidative stress, leading to a neurodegenerative disorder. However, the mechanism of glutamate-induced injury remains elusive. Gastrodin, a major active component of the traditional herbal agent Gastrodia elata (GE) Blume, has been recognized as a potential neuroprotective drug. In the current study, a classical injury model based on glutamate-induced cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 49 publications
1
34
0
Order By: Relevance
“…Recently, the anti-oxidative property of gastrodin has been investigated [22,27]. In this study, we could partially reverse H 2 O 2 -induced production of reactive oxygen species by treatment with gastrodin.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Recently, the anti-oxidative property of gastrodin has been investigated [22,27]. In this study, we could partially reverse H 2 O 2 -induced production of reactive oxygen species by treatment with gastrodin.…”
Section: Discussionmentioning
confidence: 95%
“…Gastrodia elata, a traditional herbal agent, is officially listed in the Chinese Pharmacopoeia [22]. Gastrodin (whose structure is exhibited in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cellular AMPK could be activated by upstream kinases like liver kinase B1 (LKB1) and Ca 2+ /calmodulin‐dependent protein kinase II (CaMKII), as well as inhibition of mitochondrial function (Yin et al, ). It was reported that GSTD could block the activation of CaMKII in neurons (Jiang et al, ). Here, our results clearly demonstrate that GSTD activated LKB1 in liver cells.…”
Section: Discussionmentioning
confidence: 99%